Personalisasi Iklan dan Brand Image dalam Meningkatkan Loyalitas Mahasiswa Gen Z - Devin Kenneth; Gafar Yoedtadi (Kiwari, 2026)
The role of the internet has evolved beyond a mere communication medium into a dominant transactional and lifestyle platform, particularly among younger generations. This study examines the influence of personalized advertising and brand image on consumer loyalty among Generation Z students at Tarumanagara University. Drawing upon theories of advertising personalization, brand image, and consumer loyalty, the study employs a quantitative research design. Data were collected from 118 respondents selected through purposive sampling and analyzed using validity and reliability testing, followed by multiple regression analysis with SPSS software. The findings reveal that both advertising personalization and brand image significantly affect consumer loyalty, with the model explaining 75.3% of the variance in customer loyalty. These results highlight the strategic importance of branding and personalized communication within the e-commerce ecosystem. Furthermore, the study demonstrates that digital communication factors—such as interactivity, user engagement intensity, and information accuracy—play a crucial role in strengthening consumer loyalty among Generation Z. The study contributes to the growing literature on digital marketing communication by emphasizing the effectiveness of personalized advertising strategies in fostering long-term customer relationships in the digital era. Fungsi internet kini telah bergeser jauh melampaui sekadar sarana komunikasi; ia telah bermetamorfosis menjadi arena transaksi utama yang secara dominan membentuk dan mendikte gaya hidup kaum muda. Studi ini difokuskan untuk menginvestigasi dampak dari personalisasi iklan serta citra merek terhadap tingkat kesetiaan konsumen, secara spesifik pada kalangan mahasiswa Gen Z di lingkungan Universitas Tarumanagara. Landasan konseptual yang digunakan berpusat pada teori-teori mengenai kustomisasi iklan, persepsi merek, dan loyalitas konsumen. Melalui pendekatan kuantitatif, data dihimpun dari 118 responden yang disaring menggunakan teknik purposive sampling. Proses pengolahan data mencakup uji validitas, reliabilitas, hingga analisis regresi dengan bantuan perangkat lunak SPSS. Temuan empiris mengonfirmasi bahwa kedua variabel independen tersebut memiliki dampak signifikan, di mana koefisien determinasi mencatat angka 75,3% dalam menjelaskan variasi loyalitas pelanggan. Hal ini menggarisbawahi urgensi strategi branding dan personalisasi pesan dalam ekosistem e-commerce. Selain itu terjelaskan juga elemen-elemen komunikasi digital, seperti tingkat interaktivitas, intensitas pelibatan pengguna, serta akurasi informasi, memegang peranan vital dalam mengokohkan loyalitas.